One-step synthesis of a heterogeneous catalyst: Cu+-decorated triazine-based g-C3N4 nanosheet formation and catalytic mechanism. Issue 4 (August 2021) - Yang, Linhai; Ren, Xuechang; Zhang, Yujie; Chen, Zuoyan; Wan, Jianxin
Abstract: Classical Fe-based Fenton catalysts have limited applications due to many disadvantages. Herein, Cu + /g-C3 N4 catalysts were successfully prepared by a one-step thermal polymerization method. The physicochemical of g-C3 N4 and Cu + /g-C3 N4 were characterized by XRD, SEM, FTIR, XPS and BET. The best performance of Cu + /g-C3 N4 (1:4) catalyst can be obtained when the doping molar ratio of CuSO4 ·5H2 O to melamine is 1:4, which appeared as flakes with abundant mesopores and the BET specific surface area is increased 2.5 times of pure g-C3 N4 . Such unique structures were constructed by embedding Cu + in triazine-based g-C3 N4 nanosheets and forming Cu‒N coordination bonds. The Cu + /g-C3 N4 (1:4) samples also exhibited the greatest Fenton-like catalytic performance under neutral conditions when the dosage of catalyst and H2 O2 were 0.5 g/L and 25 mmol/L, respectively, the degradation of RhB reached 92.9% in 10 min. Moreover, the high catalytic activity of this catalyst can be achieved at different initial pH in range of 5.0–12.0, especially in a strong alkaline environment. The investigation of the working mechanisms of the catalyst suggested that the Cu atom and g-C3 N4 were dual active sites, the degradation of pollutants mainly depends on OH radicals and other active species produced by it. A benefit of the unique structure was limited Cu leaching, which prevented secondary environmental pollution. This strategy has resulted in substantial progress in overcoming the drawbacks of traditional Fe-based Fenton catalysts and has shown great potential for applications in the field of wastewater treatment. Graphical Abstract: ga1 Highlights: One-step synthesis of Cu + -decorated triazine-based g-C3 N4 nanosheet. The high catalytic activity of this catalyst can be achieved at different initial pH in range of 5.0–12.0. The leaching of copper was limited by the unique structure of g-C3 N4 .